2014
DOI: 10.4172/2329-6674.1000126
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Proteases in Biofilm Disruption of Gram Positive Bacteria with Special Emphasis on Staphylococcus aureus Biofilms

Abstract: Bacterial biofilms are multicellular structures akin to citadels which have individual bacterial cells embedded within a matrix of a self-synthesized polymeric or proteinaceous material. Since biofilms can establish themselves on both biotic and abiotic surfaces and that bacteria residing in these complex molecular structures are much more resistant to antimicrobial agents than their planktonic equivalents, makes these entities a medical and economic nuisance. Of late, several strategies have been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Bacteria are known to secrete proteolytic enzymes into the extracellular medium for them to obtain nutrients for energy production and resources for growth and reproduction. , Some of the extracellular peptidases are also known virulence factors of pathogens. , Thus, screening for the presence of specific extracellular peptidases in pathological and environmental samples can be useful for clinical diagnostics and food safety surveillance. We tested the AMELIE biosensor with five common bacterial pathogens, namely, Serratia marcescens, Escherichia coli, Salmonella enterica, Staphylococcus aureus, and Pseudomonas aeruginosa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria are known to secrete proteolytic enzymes into the extracellular medium for them to obtain nutrients for energy production and resources for growth and reproduction. , Some of the extracellular peptidases are also known virulence factors of pathogens. , Thus, screening for the presence of specific extracellular peptidases in pathological and environmental samples can be useful for clinical diagnostics and food safety surveillance. We tested the AMELIE biosensor with five common bacterial pathogens, namely, Serratia marcescens, Escherichia coli, Salmonella enterica, Staphylococcus aureus, and Pseudomonas aeruginosa.…”
Section: Resultsmentioning
confidence: 99%
“…Peptidases, enzymes that catalyze proteolysis, are essential to a wide variety of physiological processes for normal cellular and tissue functioning such as the regulation of intracellular signal transduction and protein–peptide transportation, digestion, reproduction, innate immune responses, wound healing, and so forth. They are also involved in cancer cell proliferation and angiogenesis. Some extracellular peptidases of pathogens are known virulence factors. Their potentials as biomarkers for disease diagnostics and as drug targets for therapies are being increasingly recognized in recent years. Traditional assays for peptidases such as gel zymography , and antibody-based immunoassays , are usually slow, tedious, and costly. Numerous approaches for the biosensing of peptidases making use of their specific peptide cleaving properties to induce luminescence or electrochemical responses have been developed in recent years. Detection sensitivity can be further enhanced by coupling peptide cleavage to DNA aptamer-based amplification strategies , or cascaded enzymatic reactions. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This required further assessment by studying the aureolysin gene expression and the expression of its regulators. Aureolysin is the only metalloprotease produced by S. aureus and requires zinc ions for its activity [53]. This might provide an explanation for the downregulation of aureolysin encoding gene (aur) in the absence of zinc as it has been reported that the activity of aureolysin was inhibited by the metal chelator EDTA, the calcium chelator EGTA and the zinc-specific chelator 1,10-phenanthroline [56].…”
Section: Discussionmentioning
confidence: 99%
“…The metalloproteinase: aureolysin (Aur) is also known as protease III and is the only metalloprotease produced by S. aureus which requires zinc ions for its activity. Aureolysin is activated by auto-proteolytic cleavage initiating a proteolytic cascade of activation of other proteases [53]. The metalloprotease aureolysin plays an important role in staphylococcal inhibition of the complement system and helps S. aureus in immune system evasion through mediating the cleavage of the antimicrobial peptide LL-37 [54,55].…”
Section: Discussionmentioning
confidence: 99%